RELATIONSHIP BETWEEN FLEXIBLE WORKING ARRANGEMENT AND JOB SATISFACTION MEDIATED BY WORK-LIFE BALANCE IN PT. TIARA IMPRESA GUGUS ARTHA - Yuniarti, Aulia Dwi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine the relationship between Flexible Working Arrangement (X1) and JobSatisfaction (Y) mediated by Work-life Balance (Z) at PT Tiara Impresa Gugus Artha. This research wasconducted for six months starting from December 2020 to June 2021. The research method used was asurvey method. The affordable population in this study amounted to 110 employees. Based on Isaacand Michael's table, the number of samples in this study was 86 respondents. The sampling techniqueused is simple random sampling technique. The data analysis techniques used are: (1) analysisrequirements test which consists of validity and reliability tests. The test results state that the threevariables are valid with reliable values for the job satisfaction variable, namely 0.867, the flexibleworking arrangement variable, 0.706 and the work-life balance variable 0.840; (2) Modelsuitability test consisting of absolute fit indices, incremental fit indices and parsimony fit indices.The test results stated that the three variables were fit; (4) The hypothesis test in this study used SEMAMOS 21. In this study, the detection test of the intervening variable was carried out using the Sobeltest. The results show that work-life balance mediates the relationship between flexible workingarrangements and job satisfaction.